Inflamação, homeostase do ferro e suplementação nutricional na cirurgia de derivação gástrica em Y de Roux em mulheres obesas - Marin, Flávia Andréia [UNESP] (2014)
Bariatric surgery has been proven effective for controlling severe obesity and its comorbidities, but it may have complications, such as iron deficiency and anemia, especially in women of childbearing age. Obesity is associated with inflammation and changes in iron homeostasis, which tend to improve with surgery. However, this improvement raises questions regarding the relationship between iron status and the presence of comorbidities, and the role of mic ronutrient supplementation given the new nutritional requirements. This work consisted of two stages. The first stage was a retrospective analysis of women who were either hypertensive, diabetic, or comorbidity-free before surgery to verify the effect of bariatric surgery on their serum ferritin six months after surgery. The second stage consisted of a prospective study that analyzed the effect of micronutrient supplementation before and 6 months after Roux-en-Y gastric bypass (RYGB) on the inflammation and iron homeostasis of obese women. Sample and methods: The study women were 20 to 45 years old and had a body mass index (BMI) of 35 kg/m2 or more. The first stage divided 200 women into three groups: women with high blood pressure (HBP, n=70); women with type 2 diabetes (T2D, n=40), and comorbidity-free women (CF, n=90). The second stage divided 45 women into two vitamin and mineral supplementation schemes: Group 1 (n=34) took one Recommended Daily Allowance (RDA) of vitamins and minerals for 30 days before surgery and two RDAs for six months after surgery; and Group 2 (n=11) took one RDA of vitamins and minerals for six months after surgery. Assessment relied on anthropometric data and laboratory tests that quantified the markers of iron metabolism and inflammation. Results: Retrospective analysis showed that serum ferritin was higher in diabetic women but decreased six months after surgery in women with comorbidities; HBP and DM2 were determinants of the reduction. The prospective ...